Digital media in Serbia: Uses and risks - Radojković, Miroljub (Politeia, 2017)
This article presents the overview of the distribution and consequences of the use of digital media in Serbia based on the systematization of the answers to four research questions. By the opinion of the author, when we say digital media, we should consider at least five types of institutions. These are: all mass media that have done convergence with digital, information-communication technology; electronic media that have switched to program diffusion through 'Internet protocol'; web sites and portals which fulfill the legal norms to become mass media; public announcements via blogs and posts by the individuals on social networks; and cultural institutions which improve interactions with their audience through Internet. The article lists the numerous advantages of digital media that are inevitably multiplied. On the other hand, the risks and menaces caused by this trend are also listed. In conclusion, it is ascertained that media and cultural institutions cannot just archive huge production of information and cultural and/or quasi cultural, artistic products, and that the burden of selection and responsibility falls on the shoulder of the users.